Finite element analysis of composite materials using Abaqus - Barbero, Ever J. (Composite materials (CRC Press), 2013)
"Completely revised and updated, this book is a new version of Finite Element Analysis of Composite Materials with worked examples rewritten in Abaqus software instead of ANSYS. Based on one of the best-known textbooks on finite element analysis of composite materials, it reflects the state of the art in modeling. The original book will also be updated but will provide ANSYS problems"--